Does family matter? Exploring the role of family background on impostor syndrome among successful Finnish university students - Nori, Hanna; Vanttaja, Markku (Springer Science and Business Media LLC, 2026)
This study explores how family background shapes impostor syndrome (IS) among academically successful Finnish university students. While IS is commonly framed as an individual psychological phenomenon, this study emphasises its sociocultural dimensions by examining the influence of family socioeconomic status (SES) and parenting practices. Using survey data from 1,954 students with strong academic performance, the findings show that students from financially disadvantaged backgrounds report higher levels of IS. In multivariate models, financial situation, but not parental education or social class, uniquely predicted IS. Parental encouragement emerged as a protective factor against IS, while a modest positive association was observed between paternal expectations and impostor feelings. Gender differences were also observed, with women reporting significantly higher IS levels than men. Although the effect sizes in the regression analyses were modest, the results underscore the importance of early family experiences in shaping students’ academic self-perceptions. By integrating Bourdieu’s concept of habitus with Vygotsky’s theory of inner speech as conceptual lenses, the study highlights the interplay between structural inequality and internalised self-evaluation. These findings call for higher education policies that address not only individual psychological needs but also the broader social conditions that contribute to impostor experiences.